Synthesis and structures of photoactive manganese–carbonyl complexes derived from 2‐(pyridin‐2‐yl)‐1, 3‐benzothiazole and 2‐(quinolin‐2‐yl)‐1, 3‐benzothiazole. Issue 4 (1st April 2017) - Stenger-Smith, Jenny; Chakraborty, Indranil; Carrington, Samantha; Mascharak, Pradip
Abstract : Two photoactive Mn I –carbonyl complexes have been synthesized and their crystal structures are reported. These complexes can be utilized as trackable CO‐releasing molecules within biological milieu. Abstract : PhotoCORMs (photo‐active CO‐releasing molecules) have emerged as a class of CO donors where the CO release process can be triggered upon illumination with light of appropriate wavelength. We have recently reported an Mn‐based photoCORM, namely [MnBr(pbt)(CO)3 ] [pbt is 2‐(pyridin‐2‐yl)‐1, 3‐benzothiazole], where the CO release event can be tracked within cellular milieu by virtue of the emergence of strong blue fluorescence. In pursuit of developing more such trackable photoCORMs, we report herein the syntheses and structural characterization of two Mn I –carbonyl complexes, namely fac ‐tricarbonylchlorido[2‐(pyridin‐2‐yl)‐1, 3‐benzothiazole‐κ 2 N, N ′]manganese(I), [MnCl(C12 H8 N2 S)(CO)3 ], (1), and fac ‐tricarbonylchlorido[2‐(quinolin‐2‐yl)‐1, 3‐benzothiazole‐κ 2 N, N ′]manganese(I), [MnCl(C16 H10 N2 S)(CO)3 ], (2). In both complexes, the Mn I center resides in a distorted octahedral coordination environment. Weak intermolecular C—H…Cl contacts in complex (1) and Cl…S contacts in complex (2) consolidate their extended structures. These complexes also exhibit CO release upon exposure to low‐power broadband visible light. The apparent CO release rates for the two complexes have been measured to compare their CO donating capacity. The fluorogenic 2‐(pyridin‐2‐yl)‐1, 3‐benzothiazole and 2‐(quinolin‐2‐yl)‐1, 3‐benzothiazole ligands provide a convenient way to track the CO release event through the `turn‐ON' fluorescence which results upon de‐ligation of the ligands from their respective metal centers following CO photorelease.